Permanent Supportive Housing: Addressing Homelessness and Health Disparities? - Henwood, Benjamin F. (American Public Health Association, 2013)
Permanent supportive housing (PSH) is an intervention to address long-term homelessness. Evidence has resulted in a shift in US policy toward using PSH rather than shelters and transitional housing. Despite recognizing that individuals transitioning from homelessness to PSH experience a high burden of disease and health disparities, public health research has not considered whether and how PSH improves physical health outcomes. Based on diverse areas of research, we argue that in addition to improved access to quality health care, social determinants of health (including housing itself, neighborhood characteristics, and built environment) affect health outcomes. We identify implications for practice and research, and conclude that federal and local efforts to end long-term homelessness can interact with concurrent efforts to build healthy communities.